A tool to record and support the early development of children including those with special educational needs or disabilities. Issue 4 (November 2014) - Mengoni, Silvana E.; Oates, John
<x xml:space="preserve">Abstract</x> Early intervention is key for children with special educational needs or disabilities (SEND), and therefore early assessment is crucial. Information from parents about children's current ability and their developmental history can make valid and useful contributions to developmental assessments. Parental input is also important in early education for children with and without SEND. In England, recent changes to statutory guidance for early education highlight partnership working with parents, progress checks and continuous observation. The Early Years Developmental Journal (EYDJ), an Early Support tool primarily aimed at families, aims to support early identification and assessment for children with SEND and early education for all children. The article describes Early Support to provide a backdrop and then outlines the purpose, structure and rigorous development process of the EYDJ. Use of the EYDJ to support parents, early years education practitioners, health visitors, developmental assessments and the forthcoming English special educational needs (SEN) reforms is also described.